Hydrocarbon reserves of Gachsaran oilfield, SW Iran: Geochemical characteristics and origin. (April 2018) - Alizadeh, Bahram; Maroufi, Khaled; Fajrak, Mahdi
Abstract: Biomarkers and carbon isotope data were used to depict geochemical properties and to delineate source of the crude oils from Asmari and Bangestan reservoirs of the giant Gachsaran oilfield, SW Iran. Despite the distinct horizons of the reservoirs and severe petrophysical heterogeneity inside each reservoir, all oil samples show an identical level of thermal maturity. Furthermore, similar source-related parameters reflect identical source rock for both reservoirs. They indicate carbonate-marl source deposited in a marine environment under anoxic-suboxic conditions. Strong marine organic matter signatures of predominantly algal origin along with evidence of a terrigenous angiosperm plant contribution were detected. Geochemical evidence suggests that the Gachsaran field Asmari and Bangestan oils being sourced from a mix of organic-rich Kazhdumi and Pabdeh source rocks of Albian and Middle Eocene-Early Oligocene ages, respectively. Carbon isotope composition and V/Ni ratio signatures indicate Kazhdumi Formation as the main source rock. Meanwhile, significant presence of oleanane and less than unity values of C29 /C30 hopanes ratio demonstrate a partial contribution of Pabdeh Formation. This contradiction could be explained by two scenarios; 1) incorporating very immature non-expelled Pabdeh oils into the mature Kazhdumi oils during migration or 2) partial charge form low maturity Pabdeh oils that is insufficient to impact a typical mixed signature over the geochemical fingerprint of the reservoired oils. Additionally, geochemical similarities give rise to an assumption of reservoir and trap inter-connection for this giant field. Highlights: Gachsaran crude oils were geochemically evaluated using biomarkers and isotope data. Depositional environment conditions of the crude oil's source were characterized. Confirmation of both Kazhdumi and Pabdeh source rock signals in oils. Geochemical similarities propose reservoirs as well as trap inter-connection.